2010
DOI: 10.1253/circj.cj-09-0793
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal Development of Ca2+ Transients and Functional Sarcoplasmic Reticulum in Beating Mouse Hearts

Abstract: Background: It is generally accepted that Ca 2+ -induced Ca 2+ release is not the predominant mechanism during embryonic stages. Most studies have been conducted either on primary cultures or acutely isolated cells, in which an apparent reduction of ryanodine receptor density and alterations in the cell shape have been reported. The aim of the present study was to investigate developmental changes in Ca 2+ transients using whole hearts of mouse embryos and neonates. Methods and Results:Fluo-3 fluorescence sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…; Wang and Sobie ; Korhonen et al ; Kawamura et al. ). Neonatal ventricular myocytes of mice differ from their adult counterparts in a number of properties, including smaller size, greater currents through the Na + /Ca 2+ pump reduced outward K + currents, and reduced role of the SR to calcium release during a systole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Wang and Sobie ; Korhonen et al ; Kawamura et al. ). Neonatal ventricular myocytes of mice differ from their adult counterparts in a number of properties, including smaller size, greater currents through the Na + /Ca 2+ pump reduced outward K + currents, and reduced role of the SR to calcium release during a systole.…”
Section: Introductionmentioning
confidence: 99%
“…Species-specific models have been published for a number of species including guinea pig Rudy 1991, 1994), rat (Pandit et al 2001), mouse (Bondarenko et al 2004;Wang and Sobie 2008;Koivum€ aki et al 2009;Li et al 2010), and human (ten Tusscher et al 2004;Bueno-Orovio et al 2008) as it was found to be necessary to account for species-specific differences in current contributions to the AP. More recently, important developmental changes in cardiac electrophysiology of mouse myocytes have been identified (Nuss and Marban 1994;Wang et al 1996;Wetzel and Klitzner 1996;Wang and Duff 1997;Sabir et al 2008;Wang and Sobie 2008;Korhonen et al 2009;Kawamura et al 2010). Neonatal ventricular myocytes of mice differ from their adult counterparts in a number of properties, including smaller size, greater currents through the Na + /Ca 2+ pump reduced outward K + currents, and reduced role of the SR to calcium release during a systole.…”
Section: Introductionmentioning
confidence: 99%
“…references 29, 44]. Phosphorylation-induced enhanced thin filament responsiveness to narrower cellular Ca 2+ concentrations ranges will be advantageous to fetal muscle, where the control of intracellular Ca 2+ -levels may not be fully developed [45–47], and provide compensatory mechanisms in myopathic muscle [48], where Ca 2+ metabolism may be compromised.…”
Section: Resultsmentioning
confidence: 99%
“…Fetal mouse whole hearts at ED 10.5, 13.5, and 16.5 were obtained as previously reported (17). Briefly, the hearts were stained by immersion in a 20 M solution of the Ca 2ϩ -sensitive fluorescent indicator Fluo-3 AM (Molecular Probes, Eugene, OR) for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we used fetal mouse whole heart models to examine the effect of a SR Ca 2ϩ ATPase inhibitor on this Ca 2ϩ transient and indicated that Ca 2ϩ reuptake from the SR might be functional even on embryonic day (ED) 12.5 (17). We hypothesized that Ca 2ϩ release from the SR might be responsible for the increase in intracellular Ca 2ϩ concentration even in fetal hearts and that Ca 2ϩ transporters such as TCCs and NCXs might be involved in cardiac contraction in such hearts.…”
mentioning
confidence: 99%